Estimation of CSF Flow Resistance in the Upper Cervical Spine - Mardal, K-A.; Rutkowska, G.; Linge, S.; Haughton, V. (The neuroradiology journal, 2013)
Chiari I patients have increased CSF velocities in the foramen magnum due hypothetically to increased pressure gradients or reduced flow resistance. We calculated flow resistance in the cervical spinal canal in a group of subjects with and without the Chiari malformation. Eight subjects including healthy volunteers and Chiari I patients were studied. From 3D high resolution MR images of the cervical spine mathematical models of the subarachnoid spaces were created by means of standard programs for segmentation and discretization. Oscillatory flow through the subarachnoid space was simulated. Cross-sectional area of the subarachnoid space was computed at each level from C1 through C4 and the length of this spinal canal segment was measured. Peak caudad CSF flow velocity at each level was plotted against cross-section area. CSF volumetric flux and resistance were calculated for each subject. The correlation between velocity and resistance was calculated. In all subjects, peak velocities increased progressively from C1 to C4 by 0.6 to 0.7 cm/s per level. Spinal canal areas diminished from C1 to C5 in each subject at a rate of 0.25 to 0.29 cm2per level. Resistance averaged 4.3 pascal/ml/s in the eight subjects; 3.8 pascal/ml/s in patients with tonsilar herniation and 6.0 pascal/ml/s in volunteers. Velocity correlated inversely with resistance (R2= 0.6). CSF velocities correlated inversely with the flow resistance in the upper cervical spinal canal. Resistance tends to be lower in Chiari I patients than in healthy volunteers.